Contents Of Requirements For Sports Activities In Education Countries - Kamoliddin HUKIMAYEV (Euro Asian Journal Publishing, 2024)
In this article, sports improvement in the process of sports training includes the use of exercises that allow to have a targeted effect on the development of the athlete and ultimately increase his level of work ability
Keywords: Sport; training; development